ARTERIAL HYPERTENSION DURING THERAPY OF ONCOLOGICAL DISEASES WITH ANGIOGENESIS INHIBITORS: SERIOUS IMPEDIMENT OR CONTROLLED REACTION? - Zh. D. Kobalava; E. K. Shavarova (Опухоли головы и шеи, 2017)
Vascular endothelial growth factor signaling pathway (VSP) inhibitors are drugs for which arterial hypertension (AH) is a class effect, occurring with a frequency of up to 73 % of treated patients. Blockade of vascular endothelial growth factor or its receptor is accompanied by inhibition of the synthesis of nitric oxide, which is considered a major pathogenic mechanism for the development of AH. VSP-inhibitors therapy will be as safe as possible, if the patient prior to treatment will take a minimum assessment, allowing to identify the category of patients with high/very high cardiovascular risk. Risk evaluation is necessary not to abandon an effective therapy of VSP-inhibitors, and to provide a systematic approach to reduce the likelihood of potential cardiovascular toxicity. Blood pressure during VSP-inhibitors therapy is characterized by a rapid rise after the first dose of target therapy, as a rule, in the first cycle of treatment, ranging from no increase to double the systolic blood pressure. Usually iatrogenic AH spontaneously resolves after stopping chemotherapy. Timely prescribed antihypertensive therapy help to avoids dose reduction or interruption of the course of VSP-inhibitors, which significantly improves the survival of patients.